Understanding and Hindering the Electron Leakage in Green InP Quantum‐Dot Light‐Emitting Diodes - Tianqi Zhang; Fangqing Zhao; Pai Liu; Yangzhi Tan; Xiangtian Xiao; Zhaojin Wang; Weigao Wang; Dan Wu; Xiao Wei Sun; Jianhua Hao; Guichuan Xing; Kai Wang (Advanced Photonics Research, 2023)
Indium phosphide (InP) quantum‐dot light‐emitting diodes (QLEDs) are considered as one of the most promising candidates for emerging displays owing to their good luminous performance and environmentally friendly properties. The operation of green InP QLEDs relies on the radiative recombination of electrically generated excitons, as in most QLEDs; however, the electrons injected into green InP QLEDs can easily pass through the quantum‐dot (QD) layer, resulting in a carrier imbalance and low external quantum efficiency (EQE). Herein, the mechanism of electron leakage in green InP QLEDs is revealed. Based on comparative experiments and simulations of the carrier concentration distribution, the path of electron leakage is determined and it is found that the root cause is the large Fermi energy difference between green InP QDs and indium tin oxide (ITO). To solve this problem, an ultrathin LiF layer is applied to modify the work function of the ITO, which simultaneously hinders electron leakage and enhances hole injection. Benefiting from a more balanced carrier injection, the maximum EQE of green InP QLEDs improves from 4.70% to 9.14%. In these findings, a universal mechanism is provided for hindering electron leakage in green InP QLEDs, indicating the feasibility of developing highly efficient green InP QLEDs.